Begonia beijnenii (Begoniaceae, section Baryandra), a new species of Begonia from San Vicente, Palawan, the Philippines - Ang, Yu Pin; Tandang, Danilo N.; Rubite, Rosario R.; Bustamante, Rene Alfred Anton (Phytotaxa, 2020)
In our study, a distinctive new species of Begonia from an unexplored region of Port Barton, San Vicente, Palawan, B. beijnenii, is described and illustrated. The new species belongs to section Baryandra. It is morphologically most similar to B. hughesii, in having a 3-winged ovary with a cucullate wing and an abortive abaxial locule, tomentose petioles, and leaves that are adaxially glabrous and abaxially subglabrous. However, B. beijnenii distinctly differs by being comparatively smaller in size. It is only known from its type locality and vicinity. Comparisons with two variegated species of Palawan: B. cleopatrae and B. gironellae are also provided to aid in identification. B. beijnenii is hereby proposed to be Vulnerable (VU) D1, based on guidelines by IUCN.